Effect of Dextrose Cross-Linked Glutaraldehyde Hydrogel on Wound Healing Activity - Senthil Keerthana; Kalpana R (Wolters Kluwer Medknow Publications, 2024)
Dextrose cross-linked glutaraldehyde hydrogels are effective and promising drug delivery candidates. The addition of chitosan with dextrose resulted in the polymerization of material which resulted in the production of a gel-like structure that was highly viscous and had gelling properties. A swelling and absorption assay was conducted on the hydrogel. The dextrose cross-linked hydrogel has a higher absorption potential for distilled water followed by PBS and the least absorption was observed in the ethanol. Dextrose cross-linked hydrogel favors solubility in distilled water as compared to other solvents. The amoxicillin release by the dextrose cross-linked hydrogel was then tested. The result from drug release demonstrates that the dextrose cross-linked hydrogel released more than 55% of the amoxicillin in 2 hours and the remaining portion of the drug remaining. Therefore, it has a slow drug-release property, and it can be used for further wound-healing studies.